A Case Study Of Redtone International Berhad - Mustafa, Muhamad Sabri (2005)
The objective of this case study is to examine and understand the Malaysian tier-2 telco industry with special focus on Redtone International Berhad and its position in the market place. This case study will analyse the tier-2 telcos industry and operating environment.